BISKUIT LIMKUADE (LIMBAH KULIT ARI KEDELAI) YANG MUDAH PROSES PEMBUATANNYA KAYA GIZI DAN MENGURANGI HIPERTENSI - Adhitya Wisnu Laksono; Jundan Ahsana Muhammad; Nabila Fatiha Muntaz; Avilyan Fahrudin Churmelia; Denny Oktavina Radianto (KOLONI, 2023)
In Indonesia, almost every place has a tempe factory with various types of preparations. The large number of tempe industries in Indonesia causes an abundance of tempe processing industrial waste. The by-product of the tempeh-making process is soybean husk wasteh e. As is well known, soybean bran waste has low economic value so it needs to be innovated and further research carried out in order to produce a new product in the form of biscuits, easy to manufacture and liked by the wider community, namely limquade biscuits. Processing of biscuits made from waste soybean husk waste was carried out experimentally, namely drying the soybean epidermis which was still wet, smoothing the dry soybean epidermis, then mixing the butter with sugar and adding wheat flour, eggs, vanilla, and soybean epidermis flour so that it became dough. After that the dough is printed and in the oven for 10 minutes to produce sweet soy sauce. The soybean husk waste biscuits formed from the experimental results were carried out, then analyzed to test the benefits and feasibility. The benefits derived from biscuits from soybean husk waste are very beneficial for lowering blood pressure, out of 25 people suffering from hypertension, 20 people managed to reduce or stabilize blood pressure. Based on the feasibility test of waste soybean husk waste biscuits which were reviewed from the taste and aroma of 25 people suffering from hypertension, more than 50% of people stated that they were feasible to produce. hypertension. Keywords: Biscuits, Soybean Husk Waste, And Soybeans